Towards viscoelastic characterisation of the human ulnar nerve: An early assessment using embalmed cadavers. (February 2019) - Barberio, Carla G; Chaudhry, Tahseen; Power, Dominic M; Tan, Simon; Lawless, Bernard M; Espino, Daniel M; Wilton, Joanne C
Highlights: It is feasible to characterise human ulnar nerves using dynamic mechanical analysis. Human ulnar nerves display frequency dependent viscoelastic properties. Replacement grafts should aim to replicate the viscoelastic behaviour of a nerve. Abstract: Cubital tunnel syndrome is the most prevalent neuropathy of the ulnar nerve and its aetiology is controversial. Potential replacement materials should display similar viscoelastic properties. The purpose of this study was to assess the feasibility and merit of quantifying the frequency-dependent viscoelastic properties of proximal and distal sections of the human ulnar nerve. Four ulnar nerves ( n  = 4) were dissected from the elbows of human cadavers and sectioned at the level of the cubital tunnel into proximal and distal sections. These eight sections of the ulnar nerve were sinusoidally loaded to induce stresses between 0.05 and 0.27 MPa and the viscoelastic properties were measured between 0.5 and 24 Hz using dynamic mechanical analysis. The nerves were found to exhibit frequency-dependent viscoelastic behaviour throughout this frequency range. The median storage moduli of the proximal nerves ranged between 7.03 and 8.18 MPa, and 8.85–10.19 MPa for distal nerves, over the frequency-sweep tested. The median loss moduli of the proximal nerves ranged between 0.46 and 0.81 MPa and between 0.51 and 0.80 MPa for distal nerves. Ulnar nerves display frequency dependency viscoelasticity. Such characterisation is feasible with potential applications to suitable nerve grafts.